Humanization of the living environment as a guarantor of sustainable development of Odesa (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article considers the factors of humanization of the living environment as oneof the main principles of the sustainable development strategy of Odesa. Improving the urbanstructure in order to achieve physical, psychological and spiritual comfort of a person in anartificial environment demonstrates a human-centered approach to finding an integrated,comprehensive (economic, social, energy, economic, transport, etc.) model of a city with a highlevel of environmental quality. The analysis is focused on studying the current state of Odesa andfinding solutions to overcome the antagonism and confrontation between the existing conditionsand the universal human needs of its residents.It has been determined that humanization is based on taking into account the biological,physiological, spiritual, aesthetic, psychological and socio-cultural aspects of human needs; it isbased on social, environmental, ergonomic, functional, aesthetic, constructive, technological,economic requirements for improving the living environment and provides conditions for theformation of an environmentally, psychologically and aesthetically comfortable environment byurban planning means. The results obtained will contribute to the development of a program forthe further development of residential areas of Odesa, their reconstruction and transformation intoa comfortable, dignified and humane environment of the 21st century that best meets the level ofhuman needs.
Keywords: residential areas; humanization; living environment; reconstruction; human needs and physiological capabilities; social and planning structure; efficiency of territory use; sustainable development